Acumulación en ejecución de garantías tras la modificación de los Procesos Únicos de Ejecución - Vilela Carbajal, Karla (Revista de Derecho, 2019)
The article analyzes two postulations which might be presented in n enforcementof security process, both related to accumulation: 1) If an individual lends a sum ofmoney to another individual, the latter appoints two or more people as guarantors,each of whom guarantees the obligation with a mortgage; and 2) If an individuallends a sum of money to another individual, who offers the mortgage of two or morePrior to the analysis of both postulates two previous matters are studied: accumulationin the CPC and the enforcement of security. As regards accumulation, itsconcept, types and requisites are clarified. As regards the study of enforcement of securitythe problems around the required executive title in an enforcement of securityare analyzed.The postulates which are object of the present study are analyzed under the newnormative, since 2008, which moves around the so-called single process executions,and specifically to the norms related to enforcement of securities.
Keywords: Accumulation; enforcement of security, mortgage; executive title; single process execution